Intermittent Microwave Drying of Apple Slices: Drying Kinetics, Modeling, Rehydration Ratio and Effective Moisture Diffusivity - Nazmi İzli; Ahmet Polat (Journal of Agricultural Sciences)
In this research, thin layer drying characteristics, rehydration ratio and effective moisture diffusivity of apple were investigated using microwave dryer which has intermittent and continuous modes. Drying time varied between 25 and 215 minutes and they declined with the rise in microwave power and reduction in pulsing ratio. In an attempt to pick the optimum thin layer models for the drying applications, 8 mathematical models suited to the experimental results. On the grounds of the statistical tests evaluation, Midilli et al model which represent drying characteristics are optimally suited than other models. The highest rehydration ratio was recorded for the samples dried at 100W continuous mode and the lowest ratio at 300W continuous application. Effective moisture diffusivity values were computed by the 2nd law of Fick and changing between 3.04x10-9 and 2.53x10-8 m2 s-1. Consequently, the intermittent microwave method could be used as a favorable drying method for obtaining high-quality fruit slices or processing valuable material and continuous microwave drying can be taken as another drying approach for apple samples.